DEFENSE MECHANISM IN SIDNEY SHELDON'S ARE YOU AFRAID OF THE DARK?: A PSYCHOANALYTIC APPROACH - APRILINA , DENI (2007)
The major problem of this study is to elucidate how defense mechanism of Kelly is reflected in Sidney Sheldon's Are You Afraid of the Dark?. The objectives of the study are to analyze the novel based on its structural elements and to analyze the novel based on the psychoanalytic analysis. In analyzing Are You Afraid of the Dark?, the researcher uses qualitative method and psychoanalytic approach. The object of the study is Sydney Sheldon's Are You Afraid of the Dark?, published in 2004 by Warner Book. The data sources are primary data and secondary data sources. The primary data sources are the novel Are You Afraid of the Dark? itself and the secondary data sources are the books and websites about the author bibliography, literature and the theory of psychoanalytic approach. The method of data collection is library research. The technique of data analysis is descriptive analysis. The result of the study shows that sometimes several people are difficult to face the fact in their lives. They do not want to know the truth because they think it will hurt them. They often do defense mechanism to cover the fact. The several shocking truth in the major character makes her lonely. She loses her trust to everybody around her. That fact makes her lonely in the end.